The Value of Intraoperative Magnetic Resonance Imaging in Endoscopic Endonasal Resection of Pituitary Adenoma - Patel, Aneek; Dastagirzada, Yosef; Benjamin, Carolina; Lieberman, Seth; Lebowitz, Richard; Golfinos, John G.; Pacione, Donato (Journal of Neurological Surgery Part B: Skull Base, 2022)
Background Intraoperative magnetic resonance images (iMRIs) have been variably adopted by some centers to help increase the rate of gross total resection (GTR) of pituitary adenomas. In this comparative study, we report our institution's experience with using iMRIs for endoscopic endonasal approach (EEA) pituitary adenoma resection to better elucidate its role and potential value for pituitary surgery.Methods All adult patients who underwent EEA for a pituitary adenoma from January 2013 to September 2021 were retrospectively reviewed. GTR was defined as no residual tumor or recurrence on postoperative imaging within 6 months. Univariate analysis followed by multivariate analysis was performed with GTR as the categorical endpoint. To measure the independent effect of iMRI on GTR, propensity score matching was then performed.Results A total of 351 pituitary adenoma patients who underwent EEA were identified. The mean age was 51.2 (range: 18–90) years and 196 (55.8%) patients were female. iMRI was utilized in 87 (24.8%) cases. The overall rate of GTR was 69.2%. On multivariate analysis, low Knosp grade, low tumor volume, and the use of iMRI were predictive of GTR. There was no difference in the need for desmopressin or hydrocortisone at 90 days postoperatively.Conclusion At our institution, we report a significant absolute increase in GTR rates of 16.4% for patients undergoing an iMRI. Among iMRI patients who did not have GTR, the majority of residuals were intentionally left behind after being deemed too risky to pursue. Overall, this study suggests the high value that iMRI adds to endoscopic pituitary adenoma surgery.
Keywords: intraoperative MRI; endoscopic endonasal approach; pituitary adenoma; cavernous sinus; suprasellar cistern